2023
DOI: 10.58567/jie01010003
|View full text |Cite
|
Sign up to set email alerts
|

How does financial development environment affect regional innovation capabilities? New perspectives from digital finance and institutional quality

Abstract: Based on China's 30 provincial panel data from 2006 to 2018, this paper uses the spatial Durbin model to empirically study the influence path and transmission mechanism of financial development on regional technological innovation, and introduce digital finance environment, marketization degree, and government environmental management as an adjustment variable to verify its regulating effect on financial development and regional technological innovation. The study found that the overall promotion of digital fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Te central region has the greatest potential, and the western region has more space for development. Te consumption efect performs best in high-income regions, and this paper argues that this reason is due to the consistent tendency of capital factors and traditional production factors to pursue proft maximization [50]. Terefore, the increase in income can promote the upgrading of resident consumption through production restructuring, which is consistent with the fndings of Yu et al [51,52].…”
Section: Discussionsupporting
confidence: 60%
“…Te central region has the greatest potential, and the western region has more space for development. Te consumption efect performs best in high-income regions, and this paper argues that this reason is due to the consistent tendency of capital factors and traditional production factors to pursue proft maximization [50]. Terefore, the increase in income can promote the upgrading of resident consumption through production restructuring, which is consistent with the fndings of Yu et al [51,52].…”
Section: Discussionsupporting
confidence: 60%
“…Eder et al (2022) explored the impact of digital technology on the size of employment in Austria and demonstrated that new technological elements will increase the employment of high-skilled and low-skilled labor and reduce the employment of medium-skilled labor, thereby polarizing the employment structure [5]. Lu (2023) finds that the overall impact of the digital economy on local technological innovation is not significant based on the panel data of 30 provinces in China from 2006 to 2018 [6]. In terms of the creative effects of the digital economy, Graetz and Michaels (2018) revealed that the digitization of enterprises in the industrial sector reduces the share of employment in the sector and promotes employment in high-end services [7].…”
Section: Literature Reviewmentioning
confidence: 99%